Formation and development of teams for strategic university transformation projects: Methodological approaches - S. N. Apenko; G. Z. Efimova; M. Yu. Semenov (Obrazovanie i Nauka)
Introduction. Today, in the conditions of constant and growing uncertainty, there is the need to develop new, up-to-date methodologies for the development of university management teams, the transformation of their activities in a new environment.Aim. The present research aims to analyse methodological approaches to the formation and development of teams working on the strategic university transformation projects that meet the needs of practice and reflect the most effective ways to create and operate university project teams.Methodology and research methods. As the scientific basis of the proposed methodological approach to the effective formation and development of teams working on the strategic projects for the transformation of universities, the main theoretical provisions of the team-based approach are determined. The main research methods involved the analysis of scientific publications on the topic under study, the grouping and classification of approaches, a deep semi-formalised interview with 76 representatives of the administrative and managerial apparatus of three large Russian universities (regional classical universities from the Volga and Siberian Federal Districts of Russia), a questionnaire survey of 78 experts.Results. International experience in studying the activities of management teams of higher education institutions was summarised. The authors identified the restrictions and possibilities of using international experience in Russian universities. The scientific and practical groundwork for the formation and development of teams for the strategic university transformation projects is presented.Scientific novelty. The authors critically analysed the existing methodological approaches to the formation and development of teams for strategic university transformation projects, which reflect the most effective ways of creating and functioning university transformation project teams.Practical significance lies in justifying a set of methodological approaches to the formation and development of project teams and checking their applicability in the practice of university implementation transformation projects. The research materials can be useful to the representatives of administrative and managerial personnel, the heads of projects and programmes for the university development, and the employees participating in projects.